(untitled) (Journal of Bangladesh Academy of Sciences, 2018)
Three notions of normal property in fuzzy topological spaces using quasi-coincidence sense are introduced in this paper and relationship among these and other such notions are established. It is also shown that all these notions satisfy ‘good extension’ property. It is observed that the notions are preserved under one-one, onto, fuzzy open, fuzzy closed and fuzzy continuous mappings. Journal of Bangladesh Academy of Sciences, Vol. 42, No. 2, 201-205, 2018